An Explicit Jordan Decomposition of Companion Matrices - Bazán, F.S.V.; Gratton, S. (Trends in Computational and Applied Mathematics, 2006)
We derive a closed form for the Jordan decomposition of companion matrices including properties of generalized eigenvectors. As a consequence, we provide a formula for the inverse of confluent Vandermonde matrices and results on sensitivity of multiple roots of polynomials.